Impact of cone beam - CT on adrenal vein sampling in primary aldosteronism. Issue 124 (March 2020) - Meyrignac, Olivier; Arcis, Élise; Delchier, Marie-Charlotte; Mokrane, Fatima-Zohra; Darcourt, Jean; Rousseau, Hervé; Bouhanick, Béatrice
Highlights: CB-CT increases overall success of AVS thanks to increased right-sided selectivity. Use of CB-CT for AVS does not increase radiation exposure significantly. Use of CB-CT decreases fluoroscopy time and quantity of iodine injected. Abstract: Purpose: The aim of this study in a group of patients with primary aldosteronism was to evaluate the contribution of CB-CT (cone beam CT) to the overall success rate of adrenal vein sampling (AVS), and in particular to the selective cannulation of the right adrenal vein (RAV). Method: This was a retrospective single-center study including 91 AVS procedures performed by our consultant radiologist between March 2011 and January 2017. Fifty cases were performed with CB-CT and 50 were performed without. Angiography with CB-CT was carried out after RAV cannulation to check the accurate catheter position. For each patient, we collected technical and biochemical success rates, as well as irradiation data. Results: The overall success rate of AVS with CB-CT was 80 %, vs. 44 % without (p = 0.00046), with right-sided selectivity of 88 % vs. 49 % (p < 0.0001). There was no significant increase in radiation exposure with CB-CT (p = 0.8206). Fluoroscopy time and quantity of iodine injected were significantly lower with CB-CT than without (p = 0.0039 and p < 0.0001). Conclusion: CB-CT allows a better evaluation of the selectivity of right-sided adrenal catheterization and greatly increases the overall success rate of AVS.